Studies in the Structure of Some Ancient Scripts. IV. The Minoan “Libation Formula”. By W. С. Brice. V. A Sketch Plan on the Linear В Syllabary. By J. E. Henle - Brice, William С.
auch zum Hieroglyphenhethitischen.